PENDIDIKAN KESEHATAN TENTANG GIZI KERJA PADA PEKERJA PABRIK SEPATU X DI KOTA MOJOKERTO SEBAGAI UPAYA PENINGKATAN PRODUKTIVITAS KERJA - Mafticha, Elyana; Yuniarti, Asih Media; Saputra, Mukhammad Himawan; Syurandhari, Dwi Helynarti; Fardiansyah, Arief; Syalfina, Agustin Dwi (Jurnal Pengabdian Masyarakat, 2023)
Indonesia and the world are currently in Covid-19 Pandemic. The industrial and employment sectors are among those affected. The industry must continue and growth, where one of the keys is in labor productivity. Most of the time of meeting the nutrition needs is in working time. The workers bodies need sufficient nutrition to complete their workload. This community service aims to increase the work productivity of a shoe factory’s workers in Mojokerto through health education on fulfilling workers nutrition. This community service implementation is providing information through counseling to increase understanding of workers nutritional needs. This is an effort to increase work productivity through providing information in the hope that it can be used by workers in procedures for meeting their nutritional needs. Workers listen the information well. They also active in conducting two-way communication in asking and conveying experiences or problems in fulfilling nutrition. Workers nutritional needs fulfillment requires proper preparation, processing and packaging. At the preparatory stage, it’s required that foodstuffs are varied and in good condition or fresh. Preparation is carried out a day or some time before cooking food ingredients by doing good preparation and storage so that it can be done efficiently in cooking time. The foodstuffs processing is carried out hygienically with varied seasonings so as to overcome the monotonous menu. The finished dishes can be packaged properly in a container that is safe for workers to carry as a provision for fulfilling nutrients while in the company.